Meningkatkan Kompetensi Pedagogik Melalui Penerapan Supervisi Akademik pada Guru Sekolah Dasar di Samarinda - Warman, Warman (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
Although teachers must master the seven aspects of pedagogic competence, the fact is that some elementary school teachers in East Kutai Indonesia have not met expectations. This study aims to determine: the actions of principals in improving pedagogic competence through the application of academic supervision to elementary school teachers, and whether the actions of principals in implementing academic supervision can improve the pedagogic competence of elementary school teachers. The school action research design went through two cycles, involving 14 elementary school teachers as participants. Each participant was asked to fill out a consent form after being briefed on the research process and its benefits. The main instrument of the researcher himself, with the help of an observation sheet, interview guide, field notes, and a voice recorder. Results show the principal's action to improve pedagogic competence through the application of academic supervision begins with reflection, planning action, implementation, observation, and reflection, which is carried out in two cycles. The principal's actions in implementing academic supervision can improve the pedagogic competence of elementary school teachers. In the first cycle the average value of pedagogic competence only reached 66% (< 75%), and in the second cycle it reached 86% (> 75%). Therefore, school action research needs to be cultivated in educational institutions, because it is very effective in overcoming learning problems.